2016
DOI: 10.15252/embr.201642592
|View full text |Cite
|
Sign up to set email alerts
|

SPATA 2 promotes CYLD activity and regulates TNF ‐induced NF ‐κB signaling and cell death

Abstract: K63- and Met1-linked ubiquitylation are crucial posttranslational modifications for TNF receptor signaling. These non-degradative ubiquitylations are counteracted by deubiquitinases (DUBs), such as the enzyme CYLD, resulting in an appropriate signal strength, but the regulation of this process remains incompletely understood. Here, we describe an interaction partner of CYLD, SPATA2, which we identified by a mass spectrometry screen. We find that SPATA2 interacts via its PUB domain with CYLD, while a PUB intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…S7A; Elliott et al 2016;Schlicher et al 2016;Wagner et al 2016). We found that CYLD was not recruited to the TNF-RSC in Spata2 −/− MEFs like it was in wild-type MEFs upon TNFα stimulation but was restored by the expression of a Spata2 expression vector (Spata2 + cells) ( Fig.…”
Section: Spata2 Regulates the Tnf-rscmentioning
confidence: 99%
See 2 more Smart Citations
“…S7A; Elliott et al 2016;Schlicher et al 2016;Wagner et al 2016). We found that CYLD was not recruited to the TNF-RSC in Spata2 −/− MEFs like it was in wild-type MEFs upon TNFα stimulation but was restored by the expression of a Spata2 expression vector (Spata2 + cells) ( Fig.…”
Section: Spata2 Regulates the Tnf-rscmentioning
confidence: 99%
“…CYLD is recruited to the TNF-RSC by its interaction with the LUBAC in association with spermatogenesis-associated 2 (SPATA2) (Kupka et al 2016;Schlicher et al 2016;Wagner et al 2016). Spata2 was identified as a gene involved in mediating necroptosis from a genome-wide siRNA screen .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, interaction of USP10 with the Ras-GTPase-activating protein G3BP1 affects the catalytic activity of USP10, and the G3BP1-USP10 complex regulates the formation of stress granules in response to phosphorylation of eukaryotic initiation factor 2α or inhibition of eukaryotic initiation factor 4A (Kedersha et al, 2016;Soncini et al, 2001). Furthermore, spermatogenesis-associated protein 2 (SPATA2) acts as a scaffold protein that links CYLD to HOIL-1L-interacting protein (HOIP; also known as RNF31), an E3 ligase component of the linear ubiquitin chain assembly complex (LUBAC), and so controls the outcome of tumour necrosis factor receptor 1 (TNFR1; also known as TNFRSF1A)-mediated signalling (Elliott et al, 2016;Kupka et al, 2016;Schlicher et al, 2016;Wagner et al, 2016). In a similar manner, interactions of USP8 and AMSH (also known as STAMBP) with signal transducing adapter molecule 1 (STAM) and endosomal sorting complex required for transport III (ESCRT-III) components ensure the endosomal localization of these DUBs and thereby support their function in endocytosis (Clague and Urbe, 2017;Millard and Wood, 2006).…”
Section: Interacting Partners Of Dubsmentioning
confidence: 99%
“…Recently, four independent studies have identified a previously uncharacterised protein, spermatogenesis-associated factor 2 (SPATA2), as a critical component that links CYLD to HOIP [119122]. SPATA2 and SPATA2L had been previously identified in a DUB-wide proteomics screen as a strong interactor with CYLD [113].…”
Section: Regulation Of the Met1 Machinerymentioning
confidence: 99%